Entropy generation due to conjugate natural convection in enclosures bounded by vertical solid walls with different thicknesses - Varol, Yasin; Öztop, Hakan Fehmi; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2008)
Entropy generation due to conjugate natural convection heat transfer and fluid flow has been studied inside an enclosure with bounded by two solid massive walls from vertical sides at different thicknesses. Enclosure is differentially heated from vertical walls and horizontal walls are adiabatic. Governing equations which are written in streamfunction-vorticity form solved by finite difference technique for the governing parameters as Rayleigh number, 10(3) <= Ra <= 10(6), length ratio of solid walls as epsilon(1) (for left vertical wall) and epsilon(2) (for right vertical wall) and thermal conductivity ratio of solid to fluid (k), 1 <= k <= 10. Entropy generation contours due to fluid friction and heat transfer irreversibility, isotherms, streamlines, Nusselt numbers and velocity profiles were obtained. It is found that entropy generation increases with increasing of thermal conductivity ratio and thicknesses of the walls. Entropy generation due to heat transfer is more significant than that of fluid flow irreversibility for all values of thickness of the solid vertical walls. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: entropy generation; conjugate; natural convection; cavity